Cancer cells biomineralize ionic gold into nanoparticles-microplates via secreting defense proteins with specific gold-binding peptides. (15th April 2018) - Singh, Ajay Vikram; Jahnke, Timotheus; Kishore, Vimal; Park, Byung-Wook; Batuwangala, Madu; Bill, Joachim; Sitti, Metin
Graphical abstract: Abstract: Cancer cells have the capacity to synthesize nanoparticles (NPs). The detailed mechanism of this process is not very well documented. We report the mechanism of biomineralization of aqueous gold chloride into NPs and microplates in the breast-cancer cell line MCF7. Spherical gold NPs are synthesized in these cells in the presence of serum in the culture media by the reduction of HAuCl4 . In the absence of serum, the cells exhibit gold microplate formation through seed-mediate growth albeit slower reduction. The structural characteristics of the two types of NPs under different media conditions were confirmed using scanning electron microscopy (SEM); crystallinity and metallic properties were assessed with transmission electron microscopy (TEM) and x-ray photoelectron spectroscopy (XPS). Gold-reducing proteins, related to cell stress initiate the biomineralization of HAuCl4 in cells (under serum free conditions) as confirmed by infrared (IR) spectroscopy. MCF7 cells undergo irreversible replicative senescence when exposed to a high concentration of ionic gold and conversely remain in a dormant reversible quiescent state when exposed to a low gold concentration. The latter cellular state was achievable in the presence of the rho/ROCK inhibitor Y-27632. Proteomic analysis revealed consistent expression of specific proteins under serum and serum-free conditions. A high-throughput proteomic approach to screen gold-reducing proteins and peptide sequences was utilized and validated by quartz crystal microbalance with dissipation (QCM-D). Statement of significance: Cancer cells are known to synthesize gold nanoparticles and microstructures, which are promising for bioimaging and other therapeutic applications. However, the detailed mechanism of such biomineralization process is not well understood yet. Herein, we demonstrate that cancer cells exposed to gold ions (grown in serum/serum-free conditions) secrete shock and stress-related proteins with specific gold-binding/reducing polypeptides. Cells undergo reversible senescence and can recover normal physiology when treated with the senescence inhibitor depending on culture condition. The use of mammalian cells as microincubators for synthesis of such particles could have potential influence on their uptake and biocompatibility. This study has important implications for in-situ reduction of ionic gold to anisotropic micro-nanostructures that could be used in-vivo clinical applications and tumor photothermal therapy.